A lavagem de dinheiro no sistema normativo colombo-brasileiro : uma visão transnacional do combate - Serrano, Ivan Camilo Cedano (2010)
This project is based on the creation of a new juridical way of thinking, on the area of transnational law, which is justified by the approach of studies about the conflict in Money laundering, and consolidated apart from the concept of nation sovereignty, about which concrete answers were sought to comprehend the referred conflict. The problem in Money laundering is increased in immeasurable proportions, to such an extent that it became the scenery for high importance debates in International Organizations (Viena, 1988; Palermo, 2000; Mérida, 2003), and that many nations fear, once it destroys their economic and democratic structures. It is relevant to perform a study on money laundering to find other juridical solutions, different from those created by the international community, or else, with the signature of international agreements and the fulfillment of policies, the 40 recommendations of the GAFI-FATF comminated to be fulfilled more specifically in Latin America. Particularly in this case, a comparative law study was made between Brazil and Colombia, two nations possessing the same common denominator: the combat, the control and the prevention of this wrongdoing that crosses their boundaries and above which the stigma of being a drug producer and the route of drugs, respectively, weighs. Methodologically, this study was divided in three parts, detailing a complex analysis on the reason for the transnational wrongdoing of laundering to be increasing constantly. First, due to its origins and causes that founded it; second, for the formulation of policies and agreements that do not possess discursive coherence and realism when facing the illegal phenomenon; and third, for the incomprehension and bad adaptation of the internal rules to the international policies, that do not concoct, or even match, once their measures and sanctions between the nations come from a sovereign willing. With these three pillars, the theoretical foundations emerged from the concept of transnational law, referring to the cosmopolitan societies as it was described by the sociologist Ulrich Beck, and adjusted on the discursive processes of the communicative action theory, proposed by the philosopher Jürgen Habermas. Regarding these two theorists as a paradigm, an epistemological study on the phenomenon of Money laundering was considered, which does not correspond to the realities of the globalized world, spread in the massification of asymmetrical speeches, originated from the international policies. In the particular case of drug trafficking and consumption, it was clear that, in order to meet goals for the eradication of the crops and to stop the drugs, they should not, therefore, be legalized; in fact, the procedures should be gauged, aiming at the extinction of this evil. As the sovereignty of nations prevents this ending, it is made necessary the transnational policy that conducts to its solution